PENTINGNYA PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG TANDA BAHAYA PADA MASA NIFAS - Mastikana, Indah; Mutiara, Sherly; Ikramah, Dara Nauratul (Transpublika Publisher, 2022)
The puerperium is a period of vulnerability for mothers; approximately 60% of maternal deaths occur after childbirth, and nearly 50% of deaths during the puerperium, including complications, occur within the first 24 hours after delivery. Unknown risks during the postpartum period are the result of postpartum mothers' lack of knowledge. This activity aims to heighten awareness of the importance of recognizing the danger signs of postpartum in the third trimester of pregnancy. This Community Service utilizes online counseling in the form of a Zoom Cloud Meeting to educate third-trimester pregnant women about the dangers of the postpartum period. This activity will include up to fifteen future mothers, postpartum mothers, and breastfeeding mothers. This activity is graded based on whether or not participants can comprehend the presented material and whether or not they are eager to ask questions. Participation in counseling activities from the beginning to the end of the activity resulted in an increase in knowledge and enthusiasm, as well as a form of concern for the participant's mother; based on the post-test results, it was determined that the seven individuals who attended the activity had increased knowledge. The majority of the participants are aged between 21 and 46 with a high school education, and are housewives.